Phylogenetic Distribution and Evolution of Type VI Secretion System in the Genus Xanthomonas - Liyanapathiranage, Prabha; Wagner, Naama; Avram, Oren; Pupko, Tal; Potnis, Neha (Frontiers in Microbiology, 2022)
The type VI secretion system (T6SS) present in many Gram-negative bacteria is a contact-dependent apparatus that can directly deliver secreted effectors or toxins into diverse neighboring cellular targets including both prokaryotic and eukaryotic organisms. Recent reverse genetics studies with T6 core gene loci have indicated the importance of functional T6SS towards overall competitive fitness in various pathogenic Xanthomonas spp. To understand the contribution of T6SS towards ecology and evolution of Xanthomonas spp., we explored the distribution of the three distinguishable T6SS clusters, i3*, i3*** and i4, in ~1,740 Xanthomonas genomes, along with their conservation, genetic organization and their evolutionary patterns in this genus. Screening genomes for core genes of each T6 cluster indicated that 40% of the sequenced strains possess two T6 clusters, with combinations of i3*** and i3* or i3*** and i4. A few strains of X. citri, phaseoli, cissicola were the exception, possessing a unique combination of i3* and i4. The findings also indicated clade-specific distribution of T6SS clusters. Phylogenetic analysis demonstrated that T6SS clusters i3* and i3*** were probably acquired by the ancestor of the genus Xanthomonas, followed by gain or loss of individual clusters upon diversification into subsequent clades. T6 i4 cluster has been acquired in recent independent events by Group 2 xanthomonads followed by its spread via horizontal dissemination across distinct clades across Group 1 and Group 2 xanthomonads. We also noted reshuffling of entire core T6 loci, as well as T6SS spike complex components, hcp and vgrG, among different species. Our findings indicate that gain or loss events of specific T6SS clusters across Xanthomonas phylogeny have not been random.